Language change and linguistic theory. II, Morphological, syntactic, and typological change - Miller, D. Gary. (Oxford : Oxford University Press, 2010)
This book investigates a large range of changes and their motivations in all parts of the grammar and lexicon. The core argument is that, in the absence of a Grand Unification Theory in linguistics, a unified account of change is impossible without ignoring the bulk of natural language changes.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Linguistic change; Linguistics